Aberrant Anatomical Variation of Maxillary Sinus Mimicking Periapical Cyst: A Report of Two Cases and Role of CBCT in Diagnosis. (23rd April 2013) - Sekerci, Ahmet Ercan; Sisman, Yildiray; Etoz, Meryem; Bulut, Duygu Goller
Abstract : Most periapical lesions are associated with microorganisms from infected root canal systems. Maxillary sinus can pose a diagnostic dilemma radiographically because of its anatomical variation which can mimic a periapical pathosis. The aim of this study was to describe two cases of aberrant anatomical variation of the maxillary sinus that presented radiographic similarities to a periapical cyst in order to call the attention of clinicians to the fact that several different diseases are able to mimic endodontic periapical lesions. An accurate assessment of this morphology was made with the help of cone-beam computed tomography (CBCT).